2023
DOI: 10.3390/app13042674
|View full text |Cite
|
Sign up to set email alerts
|

Fuzzy-PID-Based Atmosphere Packaging Gas Distribution System for Fresh Food

Abstract: The regulation process of gas distribution systems for atmosphere packaging has the characteristics of being nonlinear time varying and having hysteric delay. When the conventional proportional-integral-derivative (PID) control algorithm is applied to this kind of system, it is difficult to set the parameters as the process is time consuming and has poor reliability. For these reasons, this paper designs a gas distribution system for fresh food atmosphere packaging based on a fuzzy PID controller. The step res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…Gaining insight into the process by which nanofibrous membranes are formed is not only a captivating scientific endeavour but also beneficial for the creation of innovative supramolecular food packaging with diverse uses. Various computational techniques have been utilized to gain insights into the intricate characteristics of molecule conformational propensity, intermolecular interaction modes, selfassembled NF structures and polymer-solvent interactions at the microscopic scale [112,113]. The advancement of ES techniques has greatly facilitated the broad application of NF materials in manufacturing.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…Gaining insight into the process by which nanofibrous membranes are formed is not only a captivating scientific endeavour but also beneficial for the creation of innovative supramolecular food packaging with diverse uses. Various computational techniques have been utilized to gain insights into the intricate characteristics of molecule conformational propensity, intermolecular interaction modes, selfassembled NF structures and polymer-solvent interactions at the microscopic scale [112,113]. The advancement of ES techniques has greatly facilitated the broad application of NF materials in manufacturing.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…The concept of deep learning (Wang et al, 2016;Gao et al, 2017;Lee et al, 2017) originated from artificial neural networks and has demonstrated excellent performance in feature learning and expression, which combines low-level features to form more abstract high-level features, thus discovering the distribution characteristics of data and enhancing image quality and recognition accuracy (Yang et al, 2022;Xu et al, 2023;Zhang et al, 2023). In 2020, Raikar et al (2020) classified and graded okra fingers by comparing three models (AlexNet, GoogLeNet, and ResNet50) and employed transfer learning to train the network.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Additionally, the sliding mode control (SMC) technique was used to generate switching pulses for the voltage source converter (VSC). Haiyu Zhang et al [21] introduced a gas distribution system based on a fuzzy PID controller, where the system's mathematical model was built using the step response method, and the gas distribution control process was optimized. However, this method is subject to the influence of human factors on parameter adjustments.…”
Section: Introductionmentioning
confidence: 99%